Triggers for sudden cardiac death in the athlete - Maron, B. J. (Cardiology Clinics, 1996)
Sudden death on the athletic field is usually due to underlying cardiovascular disease. Coronary artery disease is most common in older athletes, and a variety of congenital cardiovascular malformations predominate in young competitive athletes. Of these lesions, the most common in North America is hypertrophic cardiomyopathy. A variety of coronary artery anomalies are next in frequency, with the most important being anomalous origin of left main coronary artery from the anterior sinus of Valsalva.